Antisocial Personality disorder. A case report - V. Muñoz Martinez; A. León-Parente; M.-D. Laura (European Psychiatry, 2022)
Introduction Antisocial disorder is characterised by difficulty to adapt to social norms that normally rule different aspects of the person’s conduct in adolescence and adulthood. According to DSM-V, this disorder’s prevalence stands between 0.2% and 3%, and is more frequent in men.